RURAL-URBAN MIGRATION - CAUSES AND ECONOMIC IMPACT - Ngari, Simon Wang'ombe; Mureithi, Prof. L. P (International Journal of Economics, 2017)
Purpose: This study aims at adding value to already existing literature on migration patterns by looking at other possible factors that may cause rural-urban migration like social ties and relationships among other traditional factors like age, sex, marital status, income expectations and family size. Methodology: This survey utilized National Sample Survey and Evaluation Programme (NASSEP III) framework with 12,814 randomly selected households from 1139 clusters in the urban areas, and there was 80.7 percent response rate, that is 1938 households out of a total 2401 of the selected urban participants. Conducted using secondary data collected in 1998-99 (integrated rural urban labour force survey).Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Regression analysis was used to establish the relationship between the independent and dependent variables Results:This research critically examines the effects of education on migration decision by analyzing data on level of education attained and found out that most of the migrants to the urban areas have attained no education at all while majority are only educated to primary level. The study also examines the socio-economic concepts which are attributed to rural-urban migration such as mushrooming of slum dwellings, urban unemployment, crime, environmental degradation and other social vices like drug peddling. Unique Contribution to Theory Practice and policy: This study aims at making policy recommendations based on the findings which can be of use to policy analysts as they try to cope with this phenomenon and found that the solution lies in creating employment in rural areas and controlling the expansion of urban informal sector. Finally, this study proposes areas that require further research such as the effect of technology in influencing future migration patterns from rural to urban areas.